PENGARUH KEMOTERAPI TERHADAP KADAR SUPEROXIDE DISMUTASE (SOD) PADA PENDERITA LEUKEMIA LIMFOBLASTIK AKUT (LLA) - , khalida fetriyani Ningsih, DR. dr. Sri Mulatsih, Sp.A(K) ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background. ALL is the most common malignancy in children. Primary therapy of ALL is chemotherapy. There are many chemotherapy agents are used. Some groups of them such as mtx, daunorubicine and doxorubicine produce ROS which is part of free radicals. ROS can reduce levels of antioxidant levels including SOD in the body. The decrease of SOD levels can cause DNA, lipid and protein damage resulting adverse effects until failure of treatment. Objective. To determine the impact of mtx and daunorubicine/doxorubicine cumulative dose on SOD levels in childhood ALL Methods. A retrospective cohort study was conducted on childhood ALL undergoing chemotherapy in Dr. Sardjito General Hospital on october 2011. Subjects were ALL patients aged 0-18 years and have completed the induction phase and their parents have signed proxy concent. Exclution criteria were patients with incomplete data. Risk factors for decreased SOD levels was analyzed by cox regression, hazard ratio to determine the relationship with a significance level of <0,05 Results. Of forty patients enrolled, bivariate analysis showed that mtxâ¥3000 mg/m2 could decrease SOD levels (HR 9.959 CI95% 2.819-35.183